Enterprise information system model for Royal Malaysian Navy - Chia, Won Chee (2006)
Existing war arsenals nowadays have so much involvement of high technology and sophisticated electronic gadgets, it is not surprising that the cost and cycle times of maintenance, repair and overhaul of these system increases. This is true within the Royal Malaysian Navy Organization. As to date, not much effort has been done within the Ministry of Defence to conduct studies to help the naval system become more efficient. Current research efforts on logistics, maintenance and operations are mainly focused on individual department’s need and problem. However, in order to effectively solve the sustainment problem, research should be conducted on the entire enterprise, i.e. from acquisition, infrastructure, organization, raw materials, ground level management, maintenance, supply chains and so forth to final product delivery. To accomplish this objective, a research is conducted to develop an Enterprise Information System Model for Royal Malaysian Navy as a case study. The research methodology used is a combination of qualitative and quantitative approaches. The technique involved collecting of information from the process owners through interview, observation, documents as well as forms and later transformed into Entity Relationship Diagrams and Data Flow Diagrams. Through Integrated Definition Language (IDEF0 and IDEF3), we can measure and quantify the tiers of management. The research findings successfully show the success of proposed functional model is able to be mapped into a proposed EIS model as a whole. Their relationship will ensure that they are properly aligned and synergized with each other for fast delivery, time saving, easy managing, constant monitoring and least resources demanding. The goal of this research is also to minimize non-value-added activities throughout the entire enterprise, and to generate an Enterprise Information System Model for the Royal Malaysian Navy. In general, this research methodology can contribute towards the development of EIS model for a highly regimented organization.